Prohibiting the queer body: gender affirmation, female genital cutting, and the promise of gender intelligibility - Mitchell, Matthew (Critical criminology, 2021)
Legal regulations of the body produce and seek to protect specific imaginations of the body in an idealized form - that is, not only what a body is but also what it ought to be. In this article, we apply a queer criminological approach to interrogate the regulation of the body-that-ought-to-be that has animated two legal interventions regarding body modification: the criminalization of female genital cutting (FGC), often described in law as female genital mutilation (FGM), and the regulation of gender-affirming manual hormone use. By analyzing discourses that have circulated in Australian law regarding both practices, we show how the legitimacy of a given body modification has been tied to that modification’s potential to either threaten or affirm a body’s capacity to produce intelligible gender. We contend, on this basis, that the body that the law has sought to protect in these instances is a body that is not queer.